The Influence of Digital Marketing, Brand Equity, and Brand Ambassadors on Interest in Buying Skincare: Pengaruh Digital Marketing, Ekuitas Merek, dan Duta Merek terhadap Minat Beli Skincare - Adianto, Titania Elga; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of Digital Marketing, Brand Equity, and Brand Ambassador on Buying Interest. This study uses a quantitative approach. Sampling in the study used the Probability Sampling technique, with a total of 100 respondents from Lavina Clinic Member Ms Glow. Data collection techniques using questionnaires distributed through questionnaires. The data analysis technique in this study used multiple linear regression analysis. Data processing in this study used the software program SPSS 22 (Statistical Program For the Social Sciences). The results show that: Digital Marketing has an effect on Buying Interest in Ms Glow Skincare, Brand Equity has an effect on Buying Interest in Ms Glow Skincare, and Brand Ambassador has an effect on Buying Interest in Ms Glow Skincare